Incipiência da disponibilidade de indicadores bibliométricos e altmétricos nos repositórios institucionais brasileiros - Reis, José Eduardo dos (2017)
The Institutional Repositories (IRs) have significant potential as sources of information for the preparation of metrics studies aimed at understanding the dynamics of institutional scientific activity. However, IRs have deficiencies with regard to visual externalization of their vast scientific content in the form of bibliometric and altmetric indicators. In this context, the aim of this paper was to investigate the capability of national initiatives in Open-Access IRs in the use of bibliometric and altmetric indicators based on information visualization concepts. The research method used was the exploratory case study and the analysis unit comprises 81 IRs, active in Brazilian Science and Technology (S&T) Institutions, identified in the Directory of Open Access Repositories (OpenDOAR). Quantitatively, the existence of bibliometric and altmetric indicators in the Brazilian articles was verified in the literature, as well as the existence of plug-ins for IRs that use the DSpace system and, in a qualitative way, the analysis involved national articles with the objective of verifying which bibliometric and altmetric indicators are being used by national researchers, thus guiding the indicators that were used for the analysis with Brazilian IRs. The results obtained included the identification and analysis of the presence in Brazilian RIs of bibliometric and altmetric indicators and their graphic visualization, existing plug-ins for RIs using DSpace technology and the development of a new solution. It was observed that the bibliometric indicators showed a higher rate of occurrence in the analyzed sample than altmetric indicators and paucity of IRs in providing the indicators using a visual representation. It is concluded that the discussion of the results can contribute to the understanding of the issues surrounding the use of IRs, as sources of information for the preparation and visualization of bibliometric and altmetric indicators on the dynamics of scientific activities performed by Brazilian S&T Institutions.